Comparative Analysis of Sharia Stock Prices and Returns in the Health Sector Before and During the Covid-19 Pandemic - Elif Pardiansyah; Mohamad Ainun Najib; Muhammad Abduh (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Determining the Covid-19 pandemic as a national non-natural disaster in Indonesia impacts all sectors, including the Islamic capital market. The covid-19 pandemic can send a negative signal to investors, it is expected to cause a decrease in stock prices, trading volume, and abnormal stock returns. This study aims to analyze the impact of the Covid-19 pandemic on price changes and Islamic stock returns of PT. Kalbe Farma, Tbk. The analysis technique used is the paired sample T test for normally distributed data and the Wilcoxon signed rank test for abnormally distributed data. The results of the study show that the price of sharia stocks in the health sector did not experience a significant difference either before or during the Covid-19 pandemic. Likewise, the statistical test results show that Islamic stock returns did not experience a significant difference before and during the Covid-19 pandemic, meaning that this variable did not react negatively to the Covid-19 pandemic. The implication of this research is that PT. Kalbe Farma, Tbk is expected to try to maintain stock price stability in order to maintain investor confidence and interest because a stable stock price value can increase stock returns. Share prices are influenced by the demand and supply of services or products traded by the company so PT. Kalbe Farma, Tbk can maximize performance, product innovation, and momentum to achieve optimal returns. It is hoped that this research can become additional literature material on the topic of Islamic stock analysis during the Covid-19 pandemic.